Internal Control over Accounts Receivable to Mitigate Client Payment Delays in a Creative Agency - Hafidzoh, Siti; Suhartati, Titi (LPPM Universitas Jambi, 2026)
Payment delays in accounts receivable pose a significant challenge for creative service companies due to their impact on business operations. This study aims to identify the factors contributing to accounts receivable payment delays and evaluate the implementation of internal control based on the COSO Framework at Senyawa Agency. This qualitative case study employed semi-structured interviews, non-participant observation, and document analysis. The findings indicate that payment delays are influenced by both internal and external factors, with internal factors playing a more significant role due to weaknesses in Risk Assessment, Control Activities, and Monitoring. The absence of credit background checks, creditworthiness assessments, standardized collection procedures, and periodic receivables monitoring reduces the effectiveness of internal control in preventing payment delays. These findings suggest that strengthening preventive internal control based on the COSO Framework can enhance receivables management and reduce payment delay risks in creative service companies.